PENGARUH KEPADATAN DAN KADAR AIR TERHADAP HAMBATAN PENETRASI SONDIR PADA TANAH PASIR (Studi kasus: Pasir Sungai Palu) - Bontong, Benyamin (MEKTEK, 2010)
The DCPT penatration resistance on each type of soil has a specific characteristic. The aim of this researchis to experimentally study of DCPT penetration resistance (qc and Rf) of sand for several water content (w)and dry density( d ) variation, and comparison with the same parameter of silt. The sample of sand takenfrom Palu-1â€™s bridge upstream. Test result showed that the variation of â€œwâ€ have no significant influencefor qc and Rf. The higher thed the higher the qc and Rf. The specific relation of qc, Rf , w and d of sandin comparison with silt by using charts are veryclear and usefull to interpret the soil type